Leadership by fragmented destruction after a merger: an example from a facility of acute psychiatry - Jorid Grimeland; John E. Berg (Mental Illness)
Hospitals are labor intensive facilities based on highly skilled employees. A merger of hospitals is an effort to increase and rationalize this production. Decisions behind a merger are made at the top leadership level. How this might be done is demonstrated by examples from a 36 bed acute psychiatric facility. The aim of the study was to calculate the hidden costs of fragmented destruction of parts of a total hospital supply to patients after a merger. Fragmented destruction is the deliberate stopping of activities deemed not part of the core activities of the hospital without due consideration of the impact on core activities. The proposed changes to operational expenses at a single acute psychiatric hospital were materials for the study. The changes included activities as a reduction in local laboratory service, cleaning services, closure of physiotherapy unit, closing of cultural activities and reduced productivity. The selected activities are calculated as giving an imputed gain of € 630,000 as indicated by the leadership. The not calculated costs of reducing or removing the selected activities are estimated at € 1,955,640. The cost of staff disappointment after a merger is difficult to assess, but is probably higher than assumed in the present calculations. Imputed cost containment is not attained. The calculations indicate that implemented changes may increase cost, contrary to the belief of the leadership at both the hospital level and further up in the hospital trust. Arguments in favor of a merger have to be scrutinized thoroughly for optimistic neglect of uncalculated costs of mergers. Future hospital mergers and selected fragmentation of productive tasks at ward or hospital levels should include calculations of unavoidable costs as shown in the present paper.